Posterior tibial artery flap versus radial forearm flap in oral cavity reconstruction and donor site morbidity. Issue 11 (November 2022) - Mai, L.; Mashrah, M.A.; Lin, Z.Y.; Yan, L.J.; Xie, S.; Pan, C.
Abstract: The repair of soft tissue defects after oral cavity cancer resection is challenging. The aim of this study was to compare the outcomes and donor site morbidity of the radial forearm free flap (RFF) and posterior tibial artery perforator flap (PTAF) for oral cavity reconstruction after cancer ablation. All patients who underwent oral cavity reconstruction with a RFF or PTAF between January 2017 and December 2019 were included retrospectively in this study. All flaps were harvested with a long adipofascial extension. The donor site defects were closed with a triangular full-thickness skin graft harvested adjacent to the flap. Flap outcomes and donor site complications were recorded and compared. The study included 145 patients; 30 underwent reconstruction with a RFF and 115 with a PTAF. No significant difference between the PTAF and RFF was observed concerning the flap survival rate (98.3% vs 96.7%), flap harvest time (53.39 vs 49.28 min), hospital stay (12.3 vs 15.2 days), or subjective functional and cosmetic outcomes. The PTAF showed a larger vascular calibre ( P  < 0.05), greater flap thickness ( P  = 0.002), and lower frequency of surgical site infection ( P  = 0.055) when compared to the RFF. No significant difference was observed between the pre- and postoperative ranges of ankle and wrist movements. The PTAF is an excellent alternative to the RFF for the repair of oral cavity defects, with the additional advantages of a well-hidden scar on the lower extremity, larger vascular calibre, and lower frequencies of postoperative donor site morbidities.